2023
DOI: 10.1021/acschemneuro.3c00009
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study on the Mechanism of Arsenic Neurotoxicity in the Rat Cerebral Cortex and the Protective Mechanism of Dictyophora Polysaccharides against Arsenic Neurotoxicity

Xinglai Zhang,
Hongmei Yang,
Yi Wang
et al.

Abstract: Arsenic (As) is a toxic element, and long-term exposure to As can cause neurotoxicity. The bioactive natural compound Dictyophora polysaccharide (DIP) from edible plants has been reported to reduce the toxicity of As. In this study, As poisoning was simulated by feeding As-containing feed, followed by proteomic analysis after one month of DIP treatment. The proteomic analysis showed that 145, 276, and 97 proteins were differentially expressed between the As-treated rats and control rats (As/Ctrl group), DIP-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…In our recent proteomic analysis, we identified an extensive array of proteins associated with mitochondrial functionality, oxidative stress, the ubiquitin–proteasome system (UPS), and endoplasmic reticulum (ER) stress, as well as processes related to translation, transcription, and nuclear transport. Numerous studies have identified mitochondrial dysfunction as a key factor associated with the onset of oxidative stress, which is a pivotal event in chemical-induced neurotoxicity and developmental neurotoxicity induced by arsenic exposure ( Medda et al, 2020 ; Zhang et al, 2023 ). Notably, the exposure of NPCs to NA has exhibited marked neurotoxicity, characterized by the generation of reactive oxygen species (ROS), upregulated expression of HO-1, and the enhanced presence of antioxidant proteins, such as PDXK, GSTM3, and NDUFA10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent proteomic analysis, we identified an extensive array of proteins associated with mitochondrial functionality, oxidative stress, the ubiquitin–proteasome system (UPS), and endoplasmic reticulum (ER) stress, as well as processes related to translation, transcription, and nuclear transport. Numerous studies have identified mitochondrial dysfunction as a key factor associated with the onset of oxidative stress, which is a pivotal event in chemical-induced neurotoxicity and developmental neurotoxicity induced by arsenic exposure ( Medda et al, 2020 ; Zhang et al, 2023 ). Notably, the exposure of NPCs to NA has exhibited marked neurotoxicity, characterized by the generation of reactive oxygen species (ROS), upregulated expression of HO-1, and the enhanced presence of antioxidant proteins, such as PDXK, GSTM3, and NDUFA10.…”
Section: Discussionmentioning
confidence: 99%
“…Nobiletin displays a wide range of beneficial effects against the features of NDs. However, further studies are needed to determine its primary molecular targets using proteomic-based approaches ( Zhang et al, 2013 ; Braidy et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other compounds, such as ellagic acid, resveratrol, rutin, and taurine, deserve a separate mention, since, in addition to the neuroprotective effects mentioned above, they also ameliorate As-induced cognitive and behavioral impairments in in vivo rodent models [193,204,206,289]. Recently, Dictyophora polysaccharide, a bioactive compound from medicinal and edible fungus, has been used as a tool against As neurotoxicity due its anti-inflammatory and immunomodulatory activities [290,291].…”
Section: Nutritional Interventions and Natural Compoundsmentioning
confidence: 99%